Determination of Carbon Footprint for Local Administrations: A Case Study for Ümraniye Municipality - Betül Hande GÜRSOY HAKSEVENLER; G. Nur Çelik Onat; Begüm Akpinar; Tuğba Bedel (Doğal Afetler ve Çevre Dergisi)
Since the World is facing with detrimental effects of the global warming, some precautions are needed to be taken at international, national, regional and local levels. The fact that global warming originates mostly from urbanization and cities imposes serious responsibilities for local governments. In this study, Ümraniye which is a rapidly developing and populous district was chosen as the pilot area. The carbon footprint of transportation, housing, industry, public institutions (hospitals, schools, etc.) within the district was investigated. Also the carbon footprint of Ümraniye Municipality's own activities was calculated. In this context, the data of natural gas and electricity consumption as well as the route, number, fuel type and consumption of public transport and private vehicles, collected from related institutions for 2017 were taken into consideration. According to the obtained results, the carbon footprint in the district came from housing, business and public institutions, transportation, industry at the rate of 43%, 35%, 16%, 4% respectively. Among all, it was determined that especially the effect of the electricity consumption in business and public institutions (29%) and housing (22%) were major for the carbon footprint. It was found that the impact of private vehicle use (50%) was quite high compared to public transport (12%). The carbon footprint resulting from the municipality's own activities has a low share of 3% in total. The carbon footprint per person in the district was calculated as 2.55 tonne CO2/capita.